Insider Threats: The Cybersecurity Analysis using OCTAVE Allegro which are combined with HAIS-Q - Luqman Hakim (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
There are various types of cybersecurity threat in the globe, one of which is an insider threat. Because the current vulnerability generates an insider threat, SMEs suffer. In this situation, the company suffers a loss of profit and trust. Because of the speed and intensity of cybersecurity, particularly internal threats, SMEs must conduct regular vulnerability assessments. Insider threats to cyber security are a major issue in today's environment. Insider threats come in a variety of flavours, one of which is the unintended insider threat, or UIsT. This type of threat is a real one, and it is important to understand who and how they can become an insider threat.